Genetic diversity of the prion protein gene (PRNP) coding sequence in Czech sheep and evaluation of the national breeding programme for resistance to scrapie in the Czech Republic - Stepanek, Ondrej; Horin, Petr (Journal of applied genetics, 2017)
Of 34 breeds kept in the Czech Republic 45,604 sheep were genotyped for codons 136, 154 and 171 in the prion protein gene (PRNP) during the years 2006-2014. In this cohort, haplotypes ARR, ARQ, ARH, AHQ, VRQ, AHR and ARK were detected. The haplotype AF141RQ associated with susceptibility to atypical scrapie was observed in nine out of 30 breeds analysed for this purpose. In addition, six rare nonsynonymous substitutions producing haplotypes AT137RQ, AN138RQ, AG151RQ, AH151RQ, ARL168Q and ARQE175 were identified in various breeds. Due to their low frequencies, these polymorphisms are of no potential importance for the breeding programme. With regard to their genetic particularity, Sumavka, Valachian and Cameroon breeds were screened for additional polymorphisms. Further haplotypes, AR143RQ and AS146RQ, were found in Sumavka and Cameroon, and in Valachian sheep, respectively. Frequencies of the ARR (resistance-associated), VRQ (susceptibility-associated) haplotypes, and of the most resistant ARR/ARR genotype calculated for sheep born in the years 2001-2003 and 2011-2013 documented effects of the 10 year-lasting national breeding programme. The total frequency of ARR doubled from 36.8 to 75.8 %, while the frequency of VRQ decreased from 4 to 0.7 %. The total frequency of the ARR/ARR genotype increased from 17.7 to 59 %. These data show that the national scrapie resistance breeding programme has had an important desirable effect on haplotype and genotype frequencies of PRNP in Czech sheep.
Keywords: Prion Proteins; ovce domácí; Gene Frequency; haplotypy; Breeding; Genetic Predisposition to Disease; Scrapie; Genotype; polymorfismus genetický; Česká republika; Sheep, Domestic; Haplotypes; prionová bílkovina; Sheep; Polymorphism, Genetic; chov; Breeding programme; Czech Republic; frekvence genu; PRNP; Animals; scrapie; zvířata; genotyp; Genetic diversity; genetická predispozice k nemoci